1994
DOI: 10.1002/bit.260440504
|View full text |Cite
|
Sign up to set email alerts
|

Examination of primary metabolic pathways in a murine hybridoma with carbon‐13 nuclear magnetic resonance spectroscopy

Abstract: Primary metabolism of a murine hybridoma was probed with (13)C nuclear magnetic resonance (NMR) spectroscopy. Cells cultured in a hollow fiber bioreactor were serially infused with [1-(13)C] glucose, [2-(13)C] glucose, and [3-(13)C] glutamine. In vivo spectroscopy of the culture was used in conjunction with off-line spectroscopy of the medium to determine the intracellular concentration of several metabolic intermediates and to determine fluxes for primary metabolic pathways. Intracellular concentrations of py… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
63
4
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(76 citation statements)
references
References 51 publications
(14 reference statements)
8
63
4
1
Order By: Relevance
“…The analysis revealed that, at the pyruvate branch point, the parental cells converted 51% of the pyruvate pool into acetyl-CoA via the pyruvate dehydrogenase, 48% to lactate via lactate dehydrogenase and the remaining fraction to amino acids (mainly alanine and glycine). Our data suggested little to no significant flux through the pyruvate carboxylase, confirming an observation made by previous studies on several mammalian cells in culture (Bonarius et al, 2001;Mancuso et al, 1994;Metallo et al, 2009). In contrast, the PYC-expressing cells converted 56% of the pyruvate into acetyl-CoA, 26% into oxaloacetate via the pyruvate carboxylase and only 9% into lactate.…”
Section: O Henry Y Durocher / Metabolic Engineering ] (]]]]) ]]]-]supporting
confidence: 91%
See 1 more Smart Citation
“…The analysis revealed that, at the pyruvate branch point, the parental cells converted 51% of the pyruvate pool into acetyl-CoA via the pyruvate dehydrogenase, 48% to lactate via lactate dehydrogenase and the remaining fraction to amino acids (mainly alanine and glycine). Our data suggested little to no significant flux through the pyruvate carboxylase, confirming an observation made by previous studies on several mammalian cells in culture (Bonarius et al, 2001;Mancuso et al, 1994;Metallo et al, 2009). In contrast, the PYC-expressing cells converted 56% of the pyruvate into acetyl-CoA, 26% into oxaloacetate via the pyruvate carboxylase and only 9% into lactate.…”
Section: O Henry Y Durocher / Metabolic Engineering ] (]]]]) ]]]-]supporting
confidence: 91%
“…Another approach consisted of the expression of a yeast pyruvate carboxylase (PYC) gene in mammalian cells to compensate for the apparent lack of enzymatic activities linking glycolysis and the TCA cycle. This enzyme, catalyzing the anaplerotic conversion of pyruvate to oxaloacetate, is naturally present in mammalian cells, but several isotopic tracer studies revealed that pyruvate incorporation into the TCA mainly occurs via the pyruvate dehydrogenase reaction (Bonarius et al, 2001;Mancuso et al, 1994;Metallo et al, 2009). PYC expression was shown to have a profound effect on the metabolism of several relevant cell lines, including BHK-21 cells (Irani et al, 1999), HEK-293 cells (Elias et al, 2003) and CHO cells (Kim and Lee, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…6A). PDH E1 is the rate-limiting multimeric subunit in the PDH complex; depletion of its E1α subunit causes loss of activity (31). As expected, PDH inactivation increased the levels of [3][4][5][6][7][8][9][10][11][12][13] C]-pyruvate derived from [1,[6][7][8][9][10][11][12][13] C2]-D-glucose in both mock-and, to a greater extent, HCMV-infected cells (Fig.…”
Section: Acss2-dependent Utilization Of Acetate For Lipogenesis Is Insupporting
confidence: 67%
“…Higher lactate production rates in disease models are the results of higher use of glucose than the control model based on the assumption that lactate generated by cultured cells was only derived from glucose. Our assumption was largely supported by NMR experiments with hybridoma cells (43,44). The amount of lactate derived from glutamine was not determined in our studies.…”
Section: Construction Of Podocyte Metabolic Networkmentioning
confidence: 81%